Juridical review of construction contract disputes in Indonesia - Supriyadi Supriyadi; Mohammad Gufron AZ; Kadek Wiwik Indrayanti (Faculty of Law, University of Merdeka Malang, 2022)
Nowadays, the method of resolving disputes through the judiciary has received very sharp criticism from practitioners and legal theorists. The roles and functions of the judiciary are considered to be heavy, slow, take a long time, cost a lot of money, unresponsive in seeing the public interest, and too formal and technical. The problem to be raised in this research is how to resolve construction work contract disputes in Indonesia as regulated in Law Number 2 of 2017 concerning construction services and how to compare construction work contract dispute resolutions through adjudication and arbitration. The results of this study are Based on the description in the Discussion section. It is concluded that the Construction Services Act only stipulates one settlement mechanism, namely dispute resolution out of court (non-litigation). Even in the Construction Work Contract, there is no room to make efforts to resolve disputes through court institutions. Thus, the philosophy (spirit) carried is the concept of a